HlV-RELATED BEHAVIOURS AMONG NIGERIAN IN - SCHOOL RURAL ADOLESCENTS - Enebechi, Jude C.; Nwagu, E. N. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This study investigated the HIV-Related behaviours among Nigerian in-school rural adolescents. The survey design was adopted for the study which involved a sample of 816 students selected randomly from 8 out of the 24 grammar schools in Udi L.GA. Instrument for data collection was a 4-item researcher designed questionnaire which was validated by three experts. Using the Spearman Brown correlation coefficient, the reliability index value was 0.68, showing that it was reliable. Frequencies, percentages, and chi-square statistics were used to analyze the data and fest the only null hypothesis of the study. It was found out that in-school rural adolescents in Udi exhibited HIV-related behaviours such as keeping multiple sex partners, sex without condom and sex under alcoholic intoxication. Again that keeping multiple sex partners was more prevalent among students in co-educational schools. Based on the findings, recommendations were made.